Arame Tall speaks about interaction between providers and users of climate information in Tanzania - CGIAR Research Program on Climate Change, Agriculture and Food Security (2014)
Arame Tall, CCAFS Climate Services Champion speaks of the importance of having providers of climate services interact with the users. This happened in Tanzania May 2014.